Smart farming: legal issues and challenges - Islam, Md. Asraful; Islam, Md. Zahidul; Anzum, Rabeya (Asian and African Research Centre, 2022)
Smart farming is a revolutionary concept of modern science that denotes conducting farming activities using smart devices such as, IoT, robotics, drones, and AI. It can increase the quantity and quality of products significantly while optimizing the human labour. This paper explores different legal aspects of smart farming from the viewpoint of both the farm owner and the service provider. The purpose of this study is to analyse the legal issues and challenges arising out of smart farming and to suggest some recommendations to mitigate these issues. The study uses doctrinal legal research methodology followed by exploratory and analytical approach. Both primary and secondary sources are considered for identifying and interpreting data. The study finds that without specific, dedicated, and comprehensive legal regime it is impossible to govern the legal aspects of smart farming for any country. Therefore, it is recommended that every country needs a comprehensive legal regime to mitigate the legal issues and challenges of smart farming son that optimum benefit from smart farming can be attained and at the same time farm owners and service providers can be legally protected.